Contextual success and pitfalls of mHealth service for maternal and child health in Africa: An Intervention, Context, Actors, Mechanism, and Outcome (ICAMO) framework guided systematic review of qualitative evidence - Girma Gilano; Eshetu Andarge Zeleke; Andre Dekker; Rianne Fijten (BMC, 2024)
Abstract Introduction Mobile health (mHealth) interventions have shown potential to improve maternal and child health outcomes in Africa, but their effectiveness depends on specific interventions, context, and implementation quality. Challenges such as limited infrastructure, low digital literacy, and sustainability need to be addressed. Further evaluation studies are essential to summarize the impact of mHealth interventions. Thus, this synthesis focuses on qualitative evidence of the impact of mHealth on maternal and child health in Africa to summarize such evidence to help policy decisions. Methods A qualitative systematic review guided by the concepts of Intervention, Context, Mechanism, and Outcome (ICAMO) was employed in this study. The GRADE CERQual assessment and methodological constraints tools were utilized in the review to ascertain the level of confidence in the evidence and to examine the methodological limitations. The JBI checklist for qualitative research appraisal was also consulted during the review. Results The current review contains 32 eligible studies from databases such as CINAHL, EMBASE, MEDLINE, Scopus, Web of Science, HINARI, and Cochrane Library. The review demonstrated substantial improvements in the HCP-woman relationship, communication system, maternal and child healthcare uptake, health-seeking behavior, and HCP skills. Economic capacities, maternal education, and the low quality of existing services challenged participants. Conclusion mHealth significantly improves maternal and child health outcomes in Africa. This review showed it can improve healthcare access, empower women, and contribute to the region's goal of universal health coverage. However, the challenges such as low partner support, high costs for services, and poor quality of current care as narrated by women need commitment from health authorities in the continent. The evidence from this review suggests that mHealth can be implemented to improve maternal and child health in Africa. Trial registration PROSPERO: CRD42023461425.